2005
DOI: 10.1038/sj.cdd.4401770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of staurosporine-induced apoptosis on endothelial nitric oxide synthase in transfected COS-7 cells and primary endothelial cells

Abstract: Nitric oxide (NO) may block apoptosis by inhibiting caspases via S-nitrosylation of cysteines. Here, we investigated whether effector caspases might cleave and thereby inhibit endothelial nitric oxide synthase (eNOS). Exposure of eNOS-transfected COS-7 cells and bovine aortic endothelial cells to staurosporine resulted in significant loss of 135-kDa eNOS protein and activity, and appearance of a 60-kDa eNOS fragment; effects were inhibited by the general caspase inhibitor, benzyloxycarbonyl-Val-Ala-Asp[OMe]-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…These substances bind to cell membrane phospholipids and capture free radicals, inhibiting the oxidative stress [5]. Numerous studies have clearly demonstrated the antioxidant effects of propofol in last decades [6,[9][10][11]. Similar to previous studies, the TOS and OSI change ratio in propofol groups were significantly lower than those in thiopental groups in this study.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…These substances bind to cell membrane phospholipids and capture free radicals, inhibiting the oxidative stress [5]. Numerous studies have clearly demonstrated the antioxidant effects of propofol in last decades [6,[9][10][11]. Similar to previous studies, the TOS and OSI change ratio in propofol groups were significantly lower than those in thiopental groups in this study.…”
supporting
confidence: 78%
“…Propofol (2, 6-diisopropylphenol), a currently-available sedative and anesthetic agent, is chemically similar to the endogenous antioxidant α-tocopheral (vitamin e) and, theoretically, should have similar properties [1]. Numerous studies have demonstrated antioxidant effects of propofol in vitro [9][10][11] and in vivo [6], but the effect of propofol on oxidant and antioxidant balance in dogs has not been fully evaluated.…”
mentioning
confidence: 99%
“…9 This higher level of Bcl-2 is suggested as a factor possibly contributing to the enduring survival of the senescent HDFs. As the underlying mechanism has not been clarified, we attempted to define the specific role of Bcl-2 in the development of resistance to apoptosis in senescent HDFs, using three different types of apoptotic stimuli: (1) H 2 O 2 , which induces reactive oxygen species (ROS) and causes caspase-3-dependent or independent apoptosis, depending on the cell type 10,11 ; (2) staurosporine, a kinase inhibitor, which causes caspase-3-dependent apoptosis via a mitochondrial pathway 12 ; and (3) thapsigargin, which disrupts ER Ca 2 þ stores, leading to Ca 2 þ release from the ER (endoplasmic reticulum), and unleashes mitochondrial-dependent as well as mitochondrial-independent (caspase-12-dependent) apoptotic pathways. 13 We found that when treated with H 2 O 2 , staurosporine or thapsigargin, Bcl-2 is markedly downregulated in young HDFs but not in senescent HDFs.…”
mentioning
confidence: 99%
“…NO, derived from the action of eNOS, is one of the most important mediators in the regulation of pancreatic cell function. NO can avidly scavenge superoxide anions and protect cells from oxidative stress-induced apoptosis [24][25][26]. Studies have shown that excess vascular oxidative stress that impairs nitric oxide (NO) production results in decreased NO bioactivity in patients with diabetes [27].…”
Section: Discussionmentioning
confidence: 99%